Building systems for interior designers - Binggeli, Corky (Hoboken, New Jersey Wiley, 2016)
"Building Systems for Interior Designers remains the one go-to resource that addresses the special concerns of the interior designer within the broader context of the rest of the building design team"--Provided by publisher.
Includes bibliographical references (page 398) and index.
Keywords: Buildings -- Environmental engineering; Buildings -- Mechanical equipment -- Design and construction; Buildings -- Electric equipment -- Design and construction